Experimental investigation to elucidate why tetrahydrofuran rapidly promotes methane hydrate formation kinetics: applicable to energy storage - Kumar, Asheesh; Daraboina, Nagu; Kumar, Rajnish; Linga, Praveen (Journal of Physical Chemistry C, 2016)
Methane storage as SNG (solidified natural gas) in the form of clathrate hydrates is an emerging, economically feasible and environmentally benign technology for large scale storage. Mixed tetrahydrofuran (THF)-methane (CH4) hydrates offer a paradigm shift to milder storage conditions and faster hydrate formation kinetics, providing a promising scenario to scale up the SNG technology. In this work, we synthesize mixed THF-CH4 hydrates in a high pressure microdifferential scanning calorimeter (HP mu-DSC) to elucidate the two-step hydrate formation mechanism of mixed THF-CH4 hydrate identifying the synergism between THF and CH4. Heat flow change during hydrate formation and dissociation of mixed THF-CH4 hydrates formed in the presence of 5.56 mol % THF (stoichiometric composition) were monitored. The two step-mechanism of mixed THF-CH4 hydrate formation was further confirmed by the pressure-temperature profile and visual observations with a sample volume scale -up of about 350 times that of mu-DSC experiments.